UreE-UreG Complex Facilitates Nickel Transfer and Preactivates GTPase of UreG in Helicobacter pylori - Yang, Xinming (J Biol Chem, 2015)
The pathogenicity of Helicobacter pylori relies heavily on urease, which converts urea to ammonia to neutralize the stomach acid. Incorporation of Ni(2+) into the active site of urease requires a battery of chaperones. Both metallochaperones UreE and UreG play important roles in the urease activation. In this study, we demonstrate that, in the presence of GTP and Mg(2+), UreG binds Ni(2+) with an affinity (K(d)) of ∼0.36 μm. The GTPase activity of Ni(2+)-UreG is stimulated by both K(+) (or NH(4)(+)) and HCO(3)(−) to a biologically relevant level, suggesting that K(+)/NH(4)(+) and HCO(3)(−) might serve as GTPase elements of UreG. We show that complexation of UreE and UreG results in two protein complexes, i.e. 2E-2G and 2E-G, with the former being formed only in the presence of both GTP and Mg(2+). Mutagenesis studies reveal that Arg-101 on UreE and Cys-66 on UreG are critical for stabilization of 2E-2G complex. Combined biophysical and bioassay studies show that the formation of 2E-2G complex not only facilitates nickel transfer from UreE to UreG, but also enhances the binding of GTP. This suggests that UreE might also serve as a structural scaffold for recruitment of GTP to UreG. Importantly, we demonstrate for the first time that UreE serves as a bridge to grasp Ni(2+) from HypA, subsequently donating it to UreG. The study expands our horizons on the molecular details of nickel translocation among metallochaperones UreE, UreG, and HypA, which further extends our knowledge on the urease maturation process.